Influence of Different Wood Chip Extracts Species on Color Changes and Anthocyanin Content in Synthetic Wine Solutions - António M. Jordão (Foods, 2019)
There is restricted knowledge about the potential impact of the use of different wood species on color and anthocyanin changes during the red wine aging process. This lack of knowledge is even greater when no oak wood species are used. Thus, the aim of this study was to carry out a comparative analysis of the impact of wood chip extracts from oak, acacia, and cherry species on the color characteristics and anthocyanins changes using synthetic wine solutions. In this context, several methodologies were used to quantify, color, and anthocyanins changes during the aging time studied. The results indicated that the contact between wood chip extracts and grape skin isolated anthocyanin extracts induced a decrease of color intensity (particularly red color), and the anthocyanin content in the different experimental synthetic wine solutions studied. All chromatic modifications are potentially detected by human eyes because ΔE values were much higher than 3 CIELab units. These tendencies seem to be independent of the wood species used, but are more pronounced for higher contact time between wood chip extracts and anthocyanins. The obtained results may contribute to a better understanding of the chromatic changes of red wines when aged in contact with different wood chip species.